Efficacy and safety of rifaximin in Japanese patients with hepatic encephalopathy: A phase II/III, multicenter, randomized, evaluator‐blinded, active‐controlled trial and a phase III, multicenter, open trial. Issue 6 (19th January 2018) - Suzuki, Kazuyuki; Endo, Ryujin; Takikawa, Yasuhiro; Moriyasu, Fuminori; Aoyagi, Yutaka; Moriwaki, Hisataka; Terai, Shuji; Sakaida, Isao; Sakai, Yoshiyuki; Nishiguchi, Shuhei; Ishikawa, Toru; Takagi, Hitoshi; et al.
Abstract : Aim: The efficacy and safety of rifaximin in the treatment of hepatic encephalopathy (HE) are widely known, but they have not been confirmed in Japanese patients with HE. Thus, two prospective, randomized studies (a phase II/III study and a phase III study) were carried out. Methods: Subjects with grade I or II HE and hyperammonemia were enrolled. The phase II/III study, which was a randomized, evaluator‐blinded, active‐comparator, parallel‐group study, was undertaken at 37 institutions in Japan. Treatment periods were 14 days. Eligible patients were randomized to the rifaximin group (1200 mg/day) or the lactitol group (18–36 g/day). The phase III study was carried out in the same patients previously enrolled in the phase II/III study, and they were all treated with rifaximin (1200 mg/day) for 10 weeks. Results: In the phase II/III study, 172 patients were enrolled. Blood ammonia (B‐NH3 ) concentration was significantly improved in the rifaximin group, but the difference between the two groups was not significant. The portal systemic encephalopathy index (PSE index), including HE grade, was significantly improved in both groups. In the phase III study, 87.3% of enrolled patients completed the treatment. The improved B‐NH3 concentration and PSE index were well maintained from the phase II/III study during the treatment period of the phase III study. Adverse drug reactions (ADRs) were seen in 13.4% of patients who received rifaximin, but there were no severe ADRs leading to death. Conclusion: The efficacy of rifaximin is sufficient and treatment is well tolerated in Japanese patients with HE and hyperammonemia.